Between-race differences in the effects of breast density information and information about new imaging technology on breast-health decision-making. Issue 6 (June 2016) - Manning, Mark; Purrington, Kristen; Penner, Louis; Duric, Neb; Albrecht, Terrance L.
Highlights: Breast density information increases intentions to discuss breast cancer screening. Information effect is mediated by attitudes more strongly for African–American women. Technology information moderated effects of normative behavioral expectations Abstract: Objectives: Some US states have mandated that women be informed when they have dense breasts; however, little is known about how general knowledge about breast density (BD) affects related health decision-making. We examined the effects of BD information and imaging technology information on 138 African–American (AA) and European–American (EA) women's intentions to discuss breast cancer screening with their physicians. Methods: Women were randomly assigned to receive BD information and/or imaging technology information via 2 by 2 factorial design, and completed planned behavior measures (e.g., attitudes, intentions) related to BC screening. Results: Attitudes mediated the effects of BD information, and the mediation was stronger for AA women compared to EA women. Effects were more robust for BD information compared to imaging technology information. Results of moderator analyses revealed suppressor effects of injunctive norms that were moderated by imaging technology information. Conclusion: Information about BD favorably influences women's intentions to engage in relevant breast health behaviors. Stronger attitude mediated-effects for AA women suggest greater scrutiny of BD information. Practice implications: Since BD information may influence women's intentions to discuss BC screening, strategies to effectively present BD information to AA women should be investigated given the likelihood of their increased scrutiny of BD information.